Kontribusi Tri-Aspek Al-Nash, Ilmu, Filsafat Terhadap Revitalisasi Hadharah Islam - Siregar, Asri Yanti; M, Amril; Dewi, Eva (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Civilization (Hadharah) in Islam represents a comprehensive reflection of the values of tawhid (monotheism) that underpin human life, not merely material or technological advancement. This article examines the fundamental concept of hadharah and identifies various forms of civilization from an Islamic perspective. By exploring its terminological definition, hadharah is understood as a settled way of life that gives rise to value systems, social structures, and culture grounded in divine revelation. The discussion reveals that Islamic civilization can be categorized into three main types: Hadharah al-Nash, which emphasizes the revealed texts as the source of absolute truth; Hadharah al-‘Ilm, which integrates reason and faith in the pursuit of knowledge; and Hadharah al-Falsafah, which emerges from the dialogue between Islamic thought and global philosophical traditions. This article provides a deeper understanding of the dynamics of Islamic civilization and its relevance in the modern context.